Electrolyte-independent and sustained inorganic-rich layer with functional anion aggregates for stable lithium metal electrode - Xiaoyi Wang; Zhendong Li; Qinhao Mao; Shun Wu; Yifei Cheng; Yinping Qin; Zhenlian Chen; Zhe Peng; Xiayin Yao; Deyu Wang (Advanced Powder Materials)
Lithium (Li) metal batteries (LMBs) featuring ultrahigh energy densities are expected as ones of the most prominent devices for future energy storage applications. Nevertheless, the practical application of LMBs is still plagued by the poor interfacial stability of Li metal anode. Inorganic-rich interlayer derived from anion decomposition in advanced liquid electrolytes is demonstrated as an efficient approach to stabilize the Li metal anode, however, is electrolyte-dependent with limited application conditions due to inappropriate electrolyte properties. Herein, an efficient structuration strategy is proposed to fabricate an electrolyte-independent and sustained inorganic-rich layer, by embedding a type of functional anion aggregates consisting of selected anions ionically bonded to polymerized cation clusters. The anion aggregates can progressively release anions to react with Li+ and form key components boosting the structural stability and Li+ transfer ability of the artificial layer upon cycling. This self-reinforcing working mechanism endows the artificial layer with a sustained inorganic-rich nature and promising Li protective ability during long-term cycling, while the electrolyte-independent property enables its applications in LMBs using conventional low concentration electrolytes and all-solid-state LMBs with significantly enhanced performances. This strategy establishes an alternative designing route of Li protective layers for reliable LMBs.